2019
DOI: 10.1155/2019/8907570
|View full text |Cite
|
Sign up to set email alerts
|

Wnt-GSK3β/β-Catenin Regulates the Differentiation of Dental Pulp Stem Cells into Bladder Smooth Muscle Cells

Abstract: Smooth muscle cell- (SMC-) based tissue engineering provides a promising therapeutic strategy for SMC-related disorders. It has been demonstrated that human dental pulp stem cells (DPSCs) possess the potential to differentiate into mature bladder SMCs by induction with condition medium (CM) from bladder SMC culture, in combination with the transforming growth factor-β1 (TGF-β1). However, the molecular mechanism of SMC differentiation from DPSCs has not been fully uncovered. The canonical Wnt signaling (also kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…Next to periodontal ligament, dental tissues particularly including the dental pulp are developmentally derived from the neural crest ( Chai et al, 2000 ). Human DPSCs were reported to be positive for the NCSC-marker Nestin ( Arthur et al, 2008 ) and to form dentin and dental pulp tissue in vivo , but are also able to give rise to osteoblasts, chondrocytes, adipocytes and even to NC-related melanocytes and functionally active neurons ( Gronthos et al, 2000 ; Arthur et al, 2008 ; Stevens et al, 2008 ; Jiang et al, 2019 ). In accordance with our own observations in human ITSCs, single cell-derived clonal cultures of murine DPSCs revealed highly heterogeneous gene expression levels of Nestin between individual stem cell clones.…”
Section: Heterogeneity Of Ncscs In the Oral Cavitymentioning
confidence: 99%
“…Next to periodontal ligament, dental tissues particularly including the dental pulp are developmentally derived from the neural crest ( Chai et al, 2000 ). Human DPSCs were reported to be positive for the NCSC-marker Nestin ( Arthur et al, 2008 ) and to form dentin and dental pulp tissue in vivo , but are also able to give rise to osteoblasts, chondrocytes, adipocytes and even to NC-related melanocytes and functionally active neurons ( Gronthos et al, 2000 ; Arthur et al, 2008 ; Stevens et al, 2008 ; Jiang et al, 2019 ). In accordance with our own observations in human ITSCs, single cell-derived clonal cultures of murine DPSCs revealed highly heterogeneous gene expression levels of Nestin between individual stem cell clones.…”
Section: Heterogeneity Of Ncscs In the Oral Cavitymentioning
confidence: 99%
“…Thereafter, the authors confirmed the upregulation of SMC-related genes and proteins, namely alpha smooth muscle actin (α-SMA), desmin, and calponin. In 2019, Jiang et al proved the crucial role of the canonical Wnt-GSK3β/β-catenin pathway in the differentiation of DPSCs into bladder SMCs [161]. However, these findings need to be verified in IC/BPS animal models.…”
Section: Differentiation Into Bladder Cellsmentioning
confidence: 99%
“…n.a. [160,161] -Cell injection into the bladder (2.0 × 10 6 cells in PBS). -DPSC-derived CM contains high level of FGF-2, VEGF, C-C and C-X-C chemokine families.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…While these are some examples of many aiming to regenerate specific dental tissues, other groups have focused on exploiting the regenerative potential of DPSCs, a highly pluripotent and accessible cell type. These studies have so far primarily focused on neural repair, smooth muscles regeneration, bladder tissue repair, retinal tissue repair, and bone regeneration, to name a few (25)(26)(27)(28).…”
Section: A Glimpse Into "Whole Tooth Bioengineering"mentioning
confidence: 99%